The Role of Stakeholders in the Management of Sustainable Education Financing - Kurniawati, Melia; Tularsih, Sri; Sutrisno, Sutrisno (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Sustainable education financing has become an important issue in improving educational quality and ensuring the continuity of educational systems in Indonesia. However, education financing management still faces various challenges, including financing disparities, limited fiscal capacity, weak transparency, and low stakeholder participation. Therefore, this study aims to analyze the stakeholders involved in sustainable education financing management, identify their respective roles, examine stakeholder collaboration models, and explore challenges and strategic solutions in implementing sustainable education financing in Indonesia. This study employed a qualitative approach using a literature review method. Data were collected through documentation studies from accredited national journal articles, scientific books, previous studies, and educational policy documents published between 2022 and 2026. The collected data were analyzed using content analysis techniques through data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that sustainable education financing involves four primary stakeholders, namely governments, educational institutions, communities, and the private sector, each possessing interconnected roles and responsibilities. The study also found that collaborative stakeholder models strengthen transparency, accountability, financing diversification, and institutional sustainability. However, sustainable education financing implementation still faces several challenges, such as excessive dependence on government budgets, weak governance systems, limited managerial capacity, and low stakeholder participation. Therefore, strategic solutions including digital financial governance, strengthening accountability systems, financing diversification, and stakeholder collaboration are necessary to support sustainable education financing in Indonesia. This study contributes theoretically and practically to the development of collaborative, inclusive, and sustainable education financing governance systems.